Modeling of the wave electromagnetic processes in the microwave microelectronic material - Pivnev, V. V.; Voloshchenko, P. Y.; Voloshchenko, Y. P. (EAI Endorsed Transactions on Energy Web, 2017)
In article the nonlinear electromagnetic processes in electronic material, formed by the ordered structure of discrete electronic devices of a gigabyte and terahertz ranges are considered. Based on structural and technological design of real microwave integrated circuit fragment, the analytical expressions for model describing the processes of accumulation and exchange, dissipations and redistribution of oscillatory energy caused by signal composition in interconnections of the ordered microwave structure are synthesized. The results of a research of disturbance intensity variation in uniform electromagnetic field of integrated circuit are shown on the example of a quarter-wave equivalent two-wire transmission line loaded with the semiconductor device with tunable negative conductivity.
Keywords: microwave integrated circuit; negatron; microwave electronic device; ordered structure of electronic devices; amplitude- dependent nonlinear element; microstrip transmission line; conductive interconnection; wireless interconnection; electromagnetic energy distribution; coherent electronics technology